Financial Rewards and Job Commitment Among Public Secondary School Teachers in Ogun State, Nigeria - Bawalla, Oluwatoyin Gbenga; Adenugba, Adebimpe A. (Dhaulagiri Journal of Sociology and Anthropology, 2021)
The paper aims to examine the effects of financial rewards on job commitment among public secondary school teachers in Ogun State, Nigeria. The study was anchored on the interpretative meaning of expectancy theory. The sample consisted of 750 public secondary school teachers drawn from the three senatorial districts of Ogun State. A structured questionnaire was used to elicit information on socio-demographic characteristics and types of financial rewards available to public secondary school teachers in Ogun State. The data collected were analyzed using frequency counts and percentages. The hypothesis stipulated was analyzedusing Pearson product moment. The study found out that prompt payment of teachers’ salaries induce higher commitment to teaching, public school teachers were not satisfied with the government remuneration and there was positive and strong relationship between financial rewards and teachers job commitment (r = 0.74). The study concluded that there is significant relationship between financial rewards and teachers’ job commitment. The authors recommended that the government should provide a special salary structure for government secondary school teachers like their counterparts in other professions since they are disputably the most significant group of professionals for any nation’s economy.